A comparison of selected nutritional parameters between wild and domestic meats - Fine, Lauri-Beth (My University, 2008)
Many dietary factors, especially fat, are likely to influence the risk of cardiovascular disease by, amongst others, their effects on blood cholesterol concentration. The aim of this study was to analyse the lipid, energy and protein concentrations of local South African game in comparison to domestic meats. Fatty acid profiles were determined by chloroform-methanol extraction and gas chromatographic analysis. Total protein concentrations were determined by the Lowry Method. Energy analysis was performed using bomb calorimetry. Although no consistent, distinct differences between all the wild and domestic South African meats were found, individual differences were noted within and between species. Therefore, no general consumption recommendations can be made, but some wild meats appear to be more in line with general health recommendations than domestic meats.